PENGARUH GENDER, TEKANAN KETAATAN, KOMPLEKSITAS TUGAS, PENGETAHUAN DAN PENGALAMAN TERHADAP AUDIT JUDGMENT - Hayati, Nur (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2011)
Audit judgment is a policy or consideration of the auditor in determining the result of its audit opinion that refers to the formation of an idea, opinion or estimate of an object or event. Objectives of this study is to examine how gender, comflexity of tasks, knowlwdge and experience influence ti audit judgment. Respondent of this study is auditor who works in the office of public accountants in east java., both the level of auditor junior and senior auditor. The sampling technique in this study simple random sampling. Data were obtained through questionaires sent direcly and through the mail survey (postal). Of the 118 questionaires sent, only 89 can be analyzed. Data analysis technique using multiple regression . Based on the result of statistical test, indicates that gender, did not significant affecet to the auditor judgment. Pressure of compliance, complexity of task, knowledge and experience affrect of the audit judgement.